The Effect of Exclusive Breastfeeding on Wasting in Children Under Five: A Meta-Analysis Study (Journal of Maternal and Child Health, 2019)
Background: Wasting is a form of malnutrition that has become a serious global health problem for the past few decades. Global prevalence of wasting is reported to reach 52 million or 7.7% of the under-fives. Global coverage of exclusive breastfeeding was still as low as 40%. The purpose of this study was to due a meta-analysis on the effect of exclusive breastfeeding on wasting in children under five.Subjects and Method: This was a meta-analysis study conducted from PubMed, SCOPUS, DOAJ, BASE, EBSCO, Emerald, ProQuest, ScienceDirect, ResearchGate, and Google Scholar databases. This study sought a systematic review with observational study design and multivariate-adjusted odds ratio (AOR) analysis. Wasting was defined as weight for height (WHZ) Z score